KAJIAN PENDINGINAN PASIF UNTUK MENGOPTIMASI KENYAMANAN TERMAL SEKOLAH PADA IKLIM TROPIS LEMBAP (STUDI KASUS: KB-TK PAHOA TANGERANG) - Syifa Nirmala, Kirana; Enggar Sari, Wulani (Riset Arsitektur (RISA), 2024)
Abstract - The comfort of a building is a supporting role for the user’s activities. Student activities at school, especially kindergarten students, have activities that tend to use more of a higher metabolism, so a comfortable space is an important aspect of user activity in a room for a learning environment. The object used as a study is KB-TK Pahoa Tangerang as a school where the building maximizes passive design to support teaching and learning activities. Thermal discomfort caused by high temperatures can be a distraction and have a negative impact on the teaching and learning process. This study aims to look at thermal comfort in kindergartens located in tropical environments and activities that use a lot of physical activity for learning at the kindergarten level. In this research an experimental method will be carried out using CFD (computational fluid dynamics) simulations and including activities in kindergarten to address the problem of thermal comfort, especially for children aged 4-6 years. The analysis was carried out using the PMV (predicted mean vote) which in this process included activity variables, clothing, and building physical data to determine user satisfaction and classroom thermal comfort. Direct observation of the location of the study object was carried out to obtain existing data and literature studies for reference regarding thermal comfort and passive cooling strategies. The results obtained from this study indicate that the conditions of thermal comfort in the kindergarten from morning to noon, students using the classroom show slightly warm thermal sensation. Based on the results of the existing simulation, it is continued with efforts to optimize the design to achieve thermal comfort by optimizing it through modification of the classroom model using sun protection (shading) & ventilation. The optimization percentage reached the maximum value of PMV reduction by 12,68% in ventilation optimization, and 6,55% in shading optimization. Keywords: Passive Cooling, Thermal Comfort, School, Humid Tropical Climate, Pahoa Kindergarten Tangerang